(untitled) (Biological Sciences - PJSIR, 2006)
The chemical examination of drinking water samples colleted from twenty one sampling sites in a village of Khyber Agency (Pakistan) have been reported, described and discussed. It was noted that the quality of drinking water was poor in more than 60% of the samples collected, in respect of its excessive fluoride contents, which was found in the range of 0.27-5.03 mg/l, and was therefore many times higher in most of the samples than the WHO recommended limits of 0.5 mg/l. The higher concentration of fluoride in the potable water is considered to be the main cause of dental decay among the inhabitants of the area. Certain naturally occurring materials like plastic clay, bauxite, and high alumina clay were applied to remove the excessive fluoride contents from the potable water of the area. Fluoride removal from the potable water was effectively achieved using a mixture of indigenous plastic clay, bauxite, and high alumina clay in different ratios with sand. The process is cheap and simple, with 86% removal of fluoride contents achieved from the drinking water.